Implant survivorship, functional outcomes and complications with the use of rotating hinge knee implants: a systematic review - Xu, J; von Fritsch, L; Sabah, SA; Price, AJ; Alvand, A (BioMed Central, 2022)
Background With more complex primary and revision total knee arthroplasty procedures there is often the need to use more constrained prostheses. This study aims to investigate patient-relevant outcomes following primary and revision rotating-hinged total knee arthroplasty. Methods Electronic searches were performed using four databases from their date of inception to January 2021. Relevant studies were identified, with data extracted and analysed using PRIMSA guidelines. Results Nineteen studies were included, producing a cohort of 568 primary and 413 revision rotating hinge total knee arthroplasties (TKAs). Survival was assessed at 1-, 5-, and 10-year post-implantation. Sensitivity analyses based on person-time incidence ratios (PTIRs) were prespecified for studies not reporting survival at these timepoints. From the primary hinge TKA cohort, the median survival at 1 year was 93.4% and at 10 years it was 87%. The PTIR at long-term follow-up of this primary cohort was 1.07 (95% CI 0.4–1.7) per 100 person-years. From the revision hinge TKA cohort, the median survival at 1 year was 79.6%, and at 10 years it was 65.1%. The PTIR at long term-follow-up of this revision cohort was 1.55 (95% CI 0.9–2.3) per 100 person-years. Post-operative flexion range of motion (ROM) was 110° for primary hinge TKA and 103° for revision hinge TKA. Compared with baseline, the Knee Society Score (KSS) and Knee Society Function Score (KSFS) improved for both groups post-operatively (primary: KSS 17 to 86, KSFS 28 to 58; revision: KSS 37 to 82, KSFS 34 to 61). Conclusion The quality of the evidence for patient-relevant outcomes following hinged knee arthroplasty was limited. While there is the potential for high early revision rates, where successful, large functional benefits may be achieved.